2002
DOI: 10.1515/bmte.2002.47.s1b.743
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Heating of Human Tissue Induced by Electro-Magnetic Fields of Magnetic Resonance Imaging

Abstract: The paper presents a simulation of the transient temperature distribution in the human body caused by induced eddy currents during magnetic resonance imaging (MRI). In a first simulation the validity of the used heat conduction equation was proven using a simple example of a cool-down-process of a sphere. Thereafter the heating of a phantom model with an implanted electrode placed in a MRI-System (active body coil) was examined. The resulting increase in temperature was compared with existing measurements. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The interest in magnetic resonance imaging (MRI)‐guided endoscopic examinations in interventional medicine is growing (1–4). At clinical field strength, imaging of small regions of interest obtained from endoluminal coils exhibits a higher signal‐to‐noise ratio than with external coils (5).…”
Section: Introductionmentioning
confidence: 99%
“…The interest in magnetic resonance imaging (MRI)‐guided endoscopic examinations in interventional medicine is growing (1–4). At clinical field strength, imaging of small regions of interest obtained from endoluminal coils exhibits a higher signal‐to‐noise ratio than with external coils (5).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal simulations are based on the resolution of the Pennes bio heat equation with nodal finite element. We performed a comparative study with a sphere of diameter 200 mm for which we know the analytical formulation for the for the calculation of temperature rise caused by heat convection [22]. With AMIRA, we generated two meshes S 1 and S 2 , the first mesh is built from an isosurface and the second from the input voxels.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have shown that wireless electromagnetic energy transfer through induction, radio frequency waves, or resonant evanescent coupling results in thermal effects on tissues [ 8 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The temperature of a wireless power receiver will rise as the energy is being transferred.…”
Section: Motivation and Problem Statementmentioning
confidence: 99%
“…Wireless charging can result in more serious thermal effects [ 26 , 27 , 28 ]. Wireless energy transfer can result in thermal effects on tissues is stated in many works [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 29 ]. The temperature of a wireless power receiver will rise as the energy is being transferred.…”
Section: Related Workmentioning
confidence: 99%